Benchmarking the university campus food environment and exploring student perspectives about food insecurity and healthy eating: a case study from Australia - Jemma Keat; Putu Novi Arfirsta Dharmayani; Seema Mihrshahi (BMC, 2024)
Abstract Objective To benchmark the university food environment and explore students' experiences with food insecurity and healthy eating in order to inform interventions to improve access and affordability of healthy foods for university students. Design A food environment audit was conducted on the university campus using the Uni-Food tool from April to May 2022 and was comprised of three main components, university systems and governance, campus facilities and environment, and food retail outlets. A qualitative study design was also used to conduct focus groups and semi-structured interviews with students to explore key themes regarding their experiences with food insecurity and healthy eating. Setting Macquarie University, Australia. Participants For the food environment audit 24 retail outlets on campus and for the qualitative component 29 domestic and international students enrolled at Macquarie University. Results The university only scored 27% in total for all components in the food environment audit. The results showed the need for better governance and leadership of the food environment. The qualitative component suggested that the main barriers to accessing healthy foods were related to availability, pricing, and knowledge of healthy foods. Future intervention ideas included free fruits and vegetables, food relief, discounts, improved self-catering facilities, education, and increased healthy food outlets. Conclusions Improving governance measures related to healthy eating on campus are a core priority to strengthen the food environment and students identified pricing and availability as key issues. These findings will inform effective and feasible interventions to improve food security and healthy eating on campus.